The relationship between Foreign Direct Investment, trade openness, exchange rate, and Gross Domestic Product per capita in Vietnam - Nguyen Anh Tru; Poczta-Wajda Agnieszka (Journal of Economics and Management)
This study explores the nexus between Foreign Direct Investment (FDI), trade openness, exchange rate, and Gross Domestic Product (GDP) per capita in Vietnam between 1986 and 2020.